2011
DOI: 10.1177/193229681100500313
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Biofouling of Glucose Sensors in Vivo: Role of Tissue Microhemorrhages

Abstract: Objective: Based on our in vitro study that demonstrated the adverse effects of blood clots on glucose sensor function, we hypothesized that in vivo local tissue hemorrhages, induced as a consequence of sensor implantation or sensor movement post-implantation, are responsible for unreliable readings or an unexplained loss of functionality shortly after implantation. Research Design and Methods: To investigate this issue, we utilized real-time continuous monitoring of blood glucose levels in a mouse model. Dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 16 publications
0
56
0
Order By: Relevance
“…11 This group also conducted in vivo studies on the role of erythrocyte-embedded clots on sensor function in mice. 12 Similar to Klueh and coauthors, 11,12 in the current study, the effects of protein biofouling and cellular accumulation on glucose concentration near a sensor were observed experimentally by recording the changes in response of commercially available Medtronic MiniMed SofSensors in heparinized whole blood and various blood constituents. Numerical simulations were then used to further predict mechanistic scenarios that could be used to explain the experimental observations.…”
Section: Introductionmentioning
confidence: 94%
“…11 This group also conducted in vivo studies on the role of erythrocyte-embedded clots on sensor function in mice. 12 Similar to Klueh and coauthors, 11,12 in the current study, the effects of protein biofouling and cellular accumulation on glucose concentration near a sensor were observed experimentally by recording the changes in response of commercially available Medtronic MiniMed SofSensors in heparinized whole blood and various blood constituents. Numerical simulations were then used to further predict mechanistic scenarios that could be used to explain the experimental observations.…”
Section: Introductionmentioning
confidence: 94%
“…As such, the mouse allows investigators to transcend simple histopathology studies with the identification of the cells, mediators, and mechanisms that can be targeted to overcome the tissue reactions that limit sensor function and lifespan in vivo. In fact, using various mouse models of CGM our laboratory demonstrated the critical role of mast cells, 1 macrophages, 6 and cytokines and cytokine inhibitors 6 as well as the importance of glucose metabolism by red blood cells (microhemorrhage) 2 and by inflammatory cells recruited to the site of sensor implantation. Inflammatory cells at the site of device location are detrimental to its functionality since inflammatory cells are metabolically very active.…”
Section: In This Issue Of Journal Of Diabetes Science and Technologymentioning
confidence: 99%
“…In previous studies using a continuous glucose sensor mouse model, our laboratory demonstrated the critical role of inflammatory cells contributing to the sensor performance variation in vivo. [1][2][3] The preeminent role of the mouse is the result of large number of mutant and transgenic mice and related tools (e.g., recombinant proteins, antibodies, and drugs). These tools can provide important insight into tissue reactions and glucose sensor function and have only recently been appreciated.…”
Section: In This Issue Of Journal Of Diabetes Science and Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…More recent devices have shown detection of other endogenous metabolites (e.g., lactate, glutamate, and ATP) [11] though not within the same sensing platform. However, all these more recent developments still present electrical cables through the animals' skin [9]- [12], which allow only limited movement in the animal cage. In 2012, a novel system to transmit power and receive data on completely free-moving animals has been proposed [13], and at the end of last year the possibility of the integration with a fully implantable and biocompatible multi-panel array sensor has been proposed [14].…”
Section: Introductionmentioning
confidence: 99%